Working together for more equitable water sharing solutions - Sithirith, Mak; De Silva, Sanjiv; Sok, Sao; Kong, Heng; Palmer, Neil (WorldFish, 2025)
A new video from the CGIAR Initiatives on Asian Mega-Deltas and Aquatic Foods documents work to support Cambodia to delegate the management of water, land, agriculture, fisheries, and the environment to the district level. WorldFish and the International Water Management Institute (IWMI) - working closely with Cambodia’s Inland Fisheries Research and Development Institute (IFReDI) – piloted the establishment of a District Technical Working Group to facilitate the integrated management of water resources of Beung Sneh Lake, Prey Veng Province, in Cambodia’s Tonle Sap floodplain and Mekong delta. The work is a departure from the strongly sectoral approach to natural resources management in the country and represents a fundamental policy shift that can enable natural resources planning to better reflect the shared nature of water and land resources across multiple food production systems.